Impact of human resources' knowledge and skills on SMEs' in Medan City, Indonesia - Rasmulia Sembiring (International Journal of Management, Economics and Social Sciences (IJMESS), 2016)
The purpose of this research article was to explore the influence of knowledge and skills of human resource on the performance of culinary Small and Medium Enterprises (SMEs) in Medan City, Indonesia. Using quantitative research design, data were collected from 120 culinary SMEs located in Medan City. Multiple regression, t-test and f-ratio were used to estimate the significant effect of human knowledge and skills partially or not, whereas F test was applied to test whether the effect will be simultaneous. Results showed that knowledge and skills of human resources have significant and simultaneous effect on the performance of SMEs. It was also found that the knowledge and skills of human resources have a partial significant influence on the performance of SMEs. Human Resource skills factor has greater impact on the performance of SMEs as compared to human resource knowledge factor.
Keywords: J24; P13; 330; Knowledge; skills; performance; culinary SMEs; Medan city